Engineering drive–selection balance for localized population suppression with neutral dynamics - Katie Willis; Austin Burt (Proceedings of the National Academy of Sciences, 2025)
While the release of sterile males has been highly successful in suppressing some pest populations, it is impractical for many species due to the males disappearing after a single generation, necessitating large, repeated releases to maintain sufficient impact. Synthetic gene drives promise more efficient approaches since they can increase in frequency from rare, yet this also allows them to spread across a landscape, which may not always be desired. Between these two extremes are selectively neutral genetic constructs which persist at the frequency they are released, offering the potential for efficient suppression that remains localized. One way to achieve this would be to have perfect balance, at all construct frequencies, between gene drive increasing frequency and selection decreasing it. Here, we describe a way to closely approximate this balance using a toxin–antidote genetic construct that causes recessive lethality or sterility, encodes a genomic editor that makes dominant lethal or sterile edits in the genome, and provides protection against the action or consequences of the editing. Computer modeling shows that this design can be 100-fold more efficient than sterile males, increasing to 1,000-fold when released alongside a genetic booster. We describe designs for CRISPR-based molecular construction, including options that avoid using recoded genes as antidotes.